Analisis Pola Distribusi Prevalensi Ketidakcukupan Pangan di Kabupaten/Kota di Indonesia Tahun 2025 - Ana Novianti; Nely Aida; Asih Murwiati (CV. Bimbingan Belajar Assyfa, 2026)
Persistent regional disparities in food access and distribution pose significant managerial and developmental challenges for Indonesian food security. This study aims to analyze the spatial distribution patterns of food inadequacy prevalence across 514 regencies and municipalities in Indonesia in 2025 to inform more effective regional management policies. Utilizing secondary data from official government institutions, this research adopts a quantitative spatial approach using GeoDa software, performing thematic mapping, Moran’s I spatial autocorrelation, and Local Indicators of Spatial Association (LISA) analysis. The findings reveal a strong positive spatial autocorrelation (Moran’s I = 0.804), indicating that food inadequacy is not randomly distributed but forms distinct clusters. High-High clusters, or insecurity hotspots, are predominantly concentrated in Eastern Indonesia—specifically in Papua, Maluku, and East Nusa Tenggara—driven by geographical isolation and inadequate infrastructure. Conversely, Low-Low clusters are concentrated in Java and Bali, benefitting from superior economic development and market accessibility. These results conclude that food inadequacy is strongly influenced by interregional development disparities, highlighting the need for spatially integrated management strategies. Policymakers should transition toward a region-based approach, prioritizing infrastructure connectivity, strengthening local food distribution systems, and reducing socio-economic inequalities to ensure targeted and sustainable food security interventions.